2017
DOI: 10.1101/185801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sparse interaction between oligodendrocyte precursor cells (NG2+cells) and nodes of Ranvier in the central nervous system

Abstract: Regeneration of propagating action potentials at nodes of Ranvier allows nerve impulses to be conducted over long distances. Proper nodal function is believed to rely on intimate associations among axons, myelinating oligodendrocytes, and perinodal astrocytes. Studies in the optic nerve, corpus callosum, and spinal cord suggest that NG2+ cells are also key constituents of CNS nodes and that these glia may influence conduction efficacy and formation of axon collaterals. However, the prevalence of NG2+ cell proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Only 6% (4/62) of all clusters analyzed disappeared over a 2-day period along unmyelinated axon domains ( Figure 2 C). It has been reported that processes of oligodendrocyte precursor cells (OPCs) can associate with nodes and pre-nodal clusters to varying extents ( Biase et al., 2017 ; Serwanski et al., 2017 ; Thetiot et al., 2020 ). To test if OPC processes associate with Nfasca clusters where they could be held in position, we analyzed their co-localization in full transgenic olig1:mScarlet-CAAX, which have all OPC processes labeled.…”
Section: Resultsmentioning
confidence: 99%
“…Only 6% (4/62) of all clusters analyzed disappeared over a 2-day period along unmyelinated axon domains ( Figure 2 C). It has been reported that processes of oligodendrocyte precursor cells (OPCs) can associate with nodes and pre-nodal clusters to varying extents ( Biase et al., 2017 ; Serwanski et al., 2017 ; Thetiot et al., 2020 ). To test if OPC processes associate with Nfasca clusters where they could be held in position, we analyzed their co-localization in full transgenic olig1:mScarlet-CAAX, which have all OPC processes labeled.…”
Section: Resultsmentioning
confidence: 99%
“…2C). It has been reported that processes of oligodendrocyte precursor cells (OPCs) can associate with nodes and pre-nodal clusters to varying extents (Biase et al, 2017; Thetiot et al, 2020). In order to test if OPC processes preferably associate with Nfasca clusters where they could hold them in position, we analysed their association with OPC processes labelled in full transgenic Tg(olig1:mScarlet-CAAX) lines.…”
Section: Resultsmentioning
confidence: 99%